2016
DOI: 10.1002/ece3.1901
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of temperature on giant panda habitat in the north Minshan Mountains

Abstract: Understanding the impacts of meteorological factors on giant pandas is necessary for future conservation measures in response to global climate change. We integrated temperature data with three main habitat parameters (elevation, vegetation type, and bamboo species) to evaluate the influence of climate change on giant panda habitat in the northern Minshan Mountains using a habitat assessment model. Our study shows that temperature (relative importance = 25.1%) was the second most important variable influencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…Red pandas should have low metabolic rates to conserve heat and thermoregulation, especially during winter (Fei et al, ; Wei et al, ), but they also need more foraging time to maximize energy intake from less nutritious bamboo (McNab, ; Yonzon & Hunter, ). Liu, Guan, Dai, Li, and Gong () have reported temperature as the second most important determinant of giant panda distribution in the northern Minshan in China, similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Red pandas should have low metabolic rates to conserve heat and thermoregulation, especially during winter (Fei et al, ; Wei et al, ), but they also need more foraging time to maximize energy intake from less nutritious bamboo (McNab, ; Yonzon & Hunter, ). Liu, Guan, Dai, Li, and Gong () have reported temperature as the second most important determinant of giant panda distribution in the northern Minshan in China, similar to our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In general, wildlife population ranges shift toward the poles and to higher elevations under climate change conditions (Hole et al., ). Our results are coincided with previous studies at the spatial shift of giant panda habitat in northward, upward, and northwestward (Fan et al., ; Liu et al., ; Tuanmu et al., ), but vary a great deal as following: (1) The significant loss of habitat was not detected compared to the results of Songer et al. () and Fan et al.…”
Section: Discussionsupporting
confidence: 92%
“…Further, to lessen the uncertainty of projection results by different GCMs, the value of climate variables for modeling in our study was averaged based on used GCMs. The high AUC value in the Maxent model proved our results were reliable, the variable contribution and permutation importance of habitat factors in our study were consistent with previous studies of climate impacts on giant pandas (Liu et al., ; Songer et al., ), and the results from giant panda habitat selection studies that found fidelity for specific slopes override elevation and aspect because of the need to maintain balance between energy intake and expenditure (Hu, ; Schaller, ; Zhang et al., ). Moreover, our study provides a methodological case to analyze future climate variables with better accuracy and can be applied to other climate change studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Future work should analyze habitat connectivity and plan corridors to enhance the viability of giant panda populations76, particularly in southern mountain ranges where most habitat patches are smaller than the MAR. Because fragmentation of habitats may be aggravated in the future due to possible global climate change767778, it is necessary to evaluate their status within that context and investigate potential solutions.…”
Section: Discussionmentioning
confidence: 99%